**Q: Factor the expression and use the fundamental trigonometric identities to simplify:**

**cos²x sec²x -cos ²x =**

**A. cos²x cot²x**

B. cos²x

C. 1

D. sin²x

A: Start with the original problem:

cos²x sec²x – cos ²x

Now, factor out a cos ²x like so:

cos²x (sec²x – 1)

Now, we have a Pythagorean Identity that says: 1 + tan²x = sec²x

Subtract 1 from both sides to get:

tan²x = sec²x – 1

So, our problem has:

cos²x (sec²x – 1)

Sub in the Pythagorean Identity like so:

cos²x (tan²x)

Now, we also know that tanx = sinx / cosx

So, tan²x = sin²x / cos²x

Sub this in and simplify:

cos²x (tan²x) = cos²x (sin²x / cos²x) = cos²x (sin²x / cos²x) = sin²x

TADA! The answer is D!

### Like this:

Like Loading...